2015
DOI: 10.1016/j.bpj.2015.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic versus Electrical Stimulation of Human Cardiomyocytes: Modeling Insights

Abstract: Optogenetics provides an alternative to electrical stimulation to manipulate membrane voltage, and trigger or modify action potentials (APs) in excitable cells. We compare biophysically and energetically the cellular responses to direct electrical current injection versus optical stimulation mediated by genetically expressed light-sensitive ion channels, e.g., Channelrhodopsin-2 (ChR2). Using a computational model of ChR2(H134R mutant), we show that both stimulation modalities produce similar-in-morphology APs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 61 publications
3
70
0
2
Order By: Relevance
“…Then, upon confirmation of the successful delivery of ChR2 into the large‐sized DRG neurons, we tested whether their activity could be manipulated by light stimulation. We specifically compared the afferent volley induced by optical and electrical stimulation because the properties of action potentials induced by the two methods were reported to be different in vitro or in silico preparation (Williams & Entcheva, ; Ratnadurai‐Giridharan et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, upon confirmation of the successful delivery of ChR2 into the large‐sized DRG neurons, we tested whether their activity could be manipulated by light stimulation. We specifically compared the afferent volley induced by optical and electrical stimulation because the properties of action potentials induced by the two methods were reported to be different in vitro or in silico preparation (Williams & Entcheva, ; Ratnadurai‐Giridharan et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, upon confirmation of the successful delivery of ChR2 into the large-sized DRG neurons, we tested whether their activity could be manipulated by light stimulation. We specifically compared the afferent volley induced by optical and electrical stimulation because the properties of action potentials induced by the two methods were reported to be different in vitro or in silico preparation (Williams & Entcheva, 2015;Ratnadurai-Giridharan et al 2017). Our results show that (1) AAV9 preferentially transduces medium-to-large-sized DRG neurons, (2) compared with electrically elicited responses, the optically generated volleys in transduced DRG neurons have a higher sensitivity with amplitude of optical stimulation, but a lower sensitivity with stimulus frequency, and (3) afferent volleys evoked by light are sufficient to activate and recruit spinal reflex circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that this effect was attributable to variation in the native ionic currents active during the early stages of the AP, with the inward rectifying potassium current (I K1 ) playing a particularly prominent role; indeed, when the native I K1 formulation for the ventricular model was replaced by the one from the Purkinje fiber model, there was a significant improvement in optical excitability (lower threshold for excitation) in such ventricular myocytes. In a follow-up study (83), the same group demonstrated that, in spite of fundamental differences between the mechanisms of cellular depolarization, the primary determinants of electrical and optical excitability are the same (namely, dynamic variations in cardiomyocyte membrane resistance and inward rectifier current due to intrinsic properties of different cell types).…”
Section: Introductionmentioning
confidence: 99%
“…A growing range of optogenetic ion channels with various characteristics are available for researchers to experiment with, including both excitatory and inhibitory channels, and channels with different time constants . Among other applications, optogenetic techniques have been applied in the control of seizures in mice, control of cardiomyocytes, and control of behaviors in freely behaving mice …”
Section: Biophysics Of Light–tissue Interactionsmentioning
confidence: 99%